The effect of intellectual capital on firm’s performance: evidence from servicing and non-servicing sectors in Malaysia / Irene Ting Wei Kiong, Chan Yee Chuann and Lean Hooi Hooi - Kiong, Irene Ting Wei; Chuann, Chan Yee; Hooi, Lean Hooi (2011)
The purpose of this study is to discover the effect of Intellectual Capital on the performance of companies and further compare the results between servicing and non-servicing sectors. The study investigates the cross sectional variation among value creation efficiency of Malaysia public listed companies for the period 2003-2008 (6 years). The samples were divided into 2 different groups which are servicing sectors and non-servicing sectors to investigate whether there is any different implication between both sectors. The results indicated that most of the listed companies in Malaysia rely heavily on human capital. In fact, more than 70 percent of the value created in the samples was attributed to human capital. The study also shows that human capital efficiency and capital employed efficiency have significant positive effect on market valuation and profitability while structural capital efficiency has negative effect.